QoS routing in mobile ad hoc networks - Mohammed Safiq Mohammed Iqbal. (2008)
The aim of the project is to develop a new algorithm for finding the path bandwidth in a TDMA based ad hoc network. A multi-hop path is found between the source and destination by means of a suitable routing algorithm.